Technology, Context and Science in Architecture. (June 2014) - Neumann, Oliver
Digitally enhanced design processes and digital fabrication technologies have significantly expanded spatial and structural possibilities in architecture. Design and fabrication based on measurable input allow the digital processing of designs that are powerful in comparison to previously imagined spatial and material applications. However, this focus on data also limits designs by excluding social, economic, and ecological values that are related to cultural concerns central to architecture discourse and its built manifestations. Significantly, a sole focus on data that can be translated and processed results in the exclusion of information related to context from design considerations. Architectural discourse and practices must consider broad sets of references as guiding parameters; scientific developments that affect building methods and strategies therefore have to be associated to context-specific influences. While much is gained from engaging with contemporary design and fabrication technologies, architecture has to be conscious of references that exist outside of the numerical.